2023
DOI: 10.1029/2022jb026162
|View full text |Cite
|
Sign up to set email alerts
|

Crustal and Upper Mantle Velocity Structure of SE Tibet From Joint Inversion of Rayleigh Wave Phase Velocity and Teleseismic Body Wave Data

Abstract: The Tibetan Plateau is the world's largest and highest plateau resulting from the collision between the Indian and Eurasian plates that was initiated ∼50 Ma ago (Molnar & Tapponnier, 1975;Rowley, 1996). The intensive collision, subduction and related deep dynamic processes create significant crustal shortening and uplifting of the Plateau, accompanied with eastward extrusion of plateau materials (Harrison et al., 1992;Yin & Harrison, 2000). Due to the strong blockage of the rigid Yangtze Craton (YC) in the eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 125 publications
0
5
0
Order By: Relevance
“…As river incision data supported the lower crust flow model for the crustal uplift in this area (Clark et al., 2005), many magnetotelluric and seismic investigations have been conducted to image the lower crustal flow. While magnetotelluric images suggested that high electrical conductivity structures in the lower crust are localized in two continuous channels that run roughly from north to south (Bai et al., 2010), seismic images, on the other hand, showed two distinct LVZs beneath the SYRB and the SCB (e.g., Bao et al., 2015; M. Chen et al., 2014; Y. Liu et al., 2023; Shen et al., 2016; Y. Yang et al., 2020; X. Yang et al., 2023; Zhang et al., 2020). The two LVZs seem to be separated by the inner zone of the ELIP and will be referred to as eLVZ and wLVZ, respectively (Figure 7b).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As river incision data supported the lower crust flow model for the crustal uplift in this area (Clark et al., 2005), many magnetotelluric and seismic investigations have been conducted to image the lower crustal flow. While magnetotelluric images suggested that high electrical conductivity structures in the lower crust are localized in two continuous channels that run roughly from north to south (Bai et al., 2010), seismic images, on the other hand, showed two distinct LVZs beneath the SYRB and the SCB (e.g., Bao et al., 2015; M. Chen et al., 2014; Y. Liu et al., 2023; Shen et al., 2016; Y. Yang et al., 2020; X. Yang et al., 2023; Zhang et al., 2020). The two LVZs seem to be separated by the inner zone of the ELIP and will be referred to as eLVZ and wLVZ, respectively (Figure 7b).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the observed crustal anisotropy also disfavors the presence of an organized lower crust flow in the eLVZ area. In fact, all the most recent tomographic studies (e.g., Y. Yang et al., 2020; X. Yang et al., 2023; Zhang et al., 2020) showed that the eLVZ is disconnected from the wLVZ, suggesting that it has a different origin from the wLVZ, such as mantle upwelling (Z. Huang et al., 2015) or crustal thickening and partial melting in the mid‐lower crust (Zhang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations